The Impact of Self-Control as The Moderator on Knowledge, Experience, and Pocket Money Towards Investment Planning - Ruci Arizanda Rahayu; Shifa Azizah Haifa; Sarwenda Biduri; Wiwit Hariyanto (Jurnal Riset Akuntansi Terpadu, 2023)
This study aims to identify an increase in investment planning with self-control as a moderation between knowledge, experience, and pocket money for accounting students at Muhammadiyah University of Sidoarjo. Methods in research using quantitative methods. The population in this study were undergraduate students of the Accounting Study Program, Faculty of Business, Law and Social Sciences, Muhammadiyah University of Sidoarjo with a total of 532 students with a sample of 84 respondents. The data analysis technique used is the Outer Model to test the validity and reliability of the data and the Inner Model to test the hypothesis using the SmartPLS version 3.0 program tool. The results in this study indicate that the variables of financial knowledge, financial experience, and pocket money have a significant effect on investment planning. Moderately, self-control is able to moderate the variable of financial experience. However, self-control is not able to moderate financial knowledge and pocket money. The implication of this research is the need to increase financial knowledge and experience through more innovative learning and self-control to minimize consumptive behavior and manage finances properly through investment.